A multidisciplinary approach to online support for device research translation: regulatory change and clinical engagement. Issue 1 (March 2021) - Miller, Anne-Marie; Behan, Robert; Smith, Ian; Griffin, Matthew; Keane, Fionnuala; Langan, James; O'Rourke, Colm; McAleenan, Niall; Pandit, Abhay; Watson, Mark
Highlights: We assessed the potential for impact of the EUDR on medical device innovation. We identified the need for regulatory guidance and clinical engagement to support research-led innovation. We convened a multidisciplinary expert group to support objectives including the development of regulatory focused e-Learning for biomedical researchers. We focus on the medical device design and development pathway as timeline for regulatory guidance, clinical support and other aspects key to successful research translation. We built a web portal Medtech Translate to enhance regulatory guidance delivery and clinical support for device innovation. Abstract: Objectives: To promote an appreciation of the EU medical device regulatory framework in the biomedical research community and encourage greater levels of clinical engagement to further medical device research innovation, translation and effective clinical trials. Methods: An interdisciplinary, iterative, needs-based design approach was used to develop medical device regulatory training, information and clinical expertise resources. Results: A multimedia based self-paced e-Learning course focusing on the 'Fundamentals of Medical Device Design and Regulation' was produced in tandem with an interactive online web portal: Medtech Translate. Conclusions: Health research translation relies on both clinical input and regulation to drive progress and to ensure quality and safety standards from concept development to clinical investigation. A lack of regulatory awareness and access to clinical expertise has the potential to significantly impact on health research translation and ambition for market. Our interdisciplinary academic-regulator-clinical-industry led approach meets the need for a coordinated stakeholder response to support innovation and promote growth in the medical technology sector.